NEED ANALYSIS OF ENGLISH FOR ENGINEERING STUDENTS: A CASE STUDY - Dedi Hasnawan (Journal of English Language Learning, 2021)
Abstract: The purpose of this paper is to discuss the needs and abilities of engineers when it comes to the use of the English language in a learning environment. This was done in collaboration with a group of Engineering students from a Ponorogo vocational school. The purpose of this study was to ascertain how an English teacher instructs Electrical Engineering students in English. Additionally, to identify the types of English materials that the teacher and students of Electrical Engineering major require. The findings of this study indicate that all four critical language skills, particularly listening and speaking, are frequently used in the workplace. Additionally, it was discovered that technicians perceived themselves as ineffective English language users at work. They believed that some form of training would benefit their ability to communicate effectively at work. Additionally, it was noted that technicians had some unique requirements for English language proficiency that may not be covered in general English courses. The researcher will use this study to aid in the development of an English for Specific Purposes (ESP) course.Keyword: English for Specific Purpose (ESP), Need Analysis